Unmasking Boko Haram exploring global jihad in Nigeria - Zenn, Jacob (Lynne Rienner Publishers, 2020)
"A detailed chronicle of the foundation of Boko Haram, its internal dynamics, and its evolution as a global Jihadist movement"--